Odpowiedzi

Najlepsza Odpowiedź!
2009-12-22T13:13:54+01:00
Doprowadź wyrażenia 2(x-3y)²-3(x-2y)+12xy do najprostszych postaci i następnie oblicz jego wartość dla x=√2 i y=√3

2(x-3y)²-3(x-2y)+12xy = 2(x²-6xy+9y²)-3x+6y+12xy = 2x²-12xy+18y²-3x+6y+12xy = 2x²-3x+18y²+6y

2(√2)²-3√2+18(√3)²+6√3 = 2*2-3√2+18*3+6√3 = 4-3√2+54+6√3 = 58-3√2+6√3
1 5 1
2009-12-22T13:31:02+01:00
Doprowadź wyrażenia 2(x-3y)²-3(x-2y)+12xy do najprostszych postaci i następnie oblicz jego wartość dla x=√2 i y=√3

2(x-3y)²-3(x-2y)+12xy=
2(x²+ 9y²- 6xy)- 3x+6y+12xy=
2x²+18y²-12xy-3x+6y+12xy=
2x²+18y²-3x+6y

dla x= √2
dla y= √3
2x²+18y²-3x+6y=
2(√2)²+ 18(√3)²- 3(√2) + 6(√3)=
2•2 + 18•3 - 3√2+ 6√3=
4+54- 3√2 + 6√3= 58-3√2+ 6√3
1 5 1
  • Użytkownik Zadane
2009-12-22T14:08:57+01:00
2(x-3y)²-3(x-2y)+12xy dla x=√2 i y=√3

2(x-3y)²-3(x-2y)+12xy = 2(x²-6xy+9y²)-3x+6y+12xy = 2x²-12xy+18y²-3x+6y+12xy = 2x²-3x+18y²+6y

2(√2)²-3√2+18(√3)²+6√3 = 2*2-3√2+18*3+6√3 = 4-3√2+54+6√3 = 58-3√2+6√3
1 5 1